Discorhabdin alkaloids from Antarctic Latrunculia spp. sponges as a new class of cholinesterase inhibitors - Botić, Tanja; Defant, Andrea; Zanini, Pietro; Žužek, Monika Cecilija; Frangež, Robert; Janussen, Dorte; Kersken, Daniel; Knez, Željko; Mancini, Ines; Sepčić, Kristina (European Journal of Medicinal Chemistry, 2017)
The brominated pyrroloiminoquinone alkaloids discorhabdins B, L and G and 3-dihydro-7,8- dehydrodiscorhabdin C, isolated from methanol extracts of two specimens of Latrunculia sp. sponges collected near the Antarctic Peninsula, are here demonstrated for the first time to be reversible competitive inhibitors of cholinesterases. They showed Ki for electric eel acetylcholinesterase of 1.6-15.0μM, for recombinant human acetylcholinesterase of 22.8-98.0μM, and for horse serum butyrylcholinesterase of 5.0-76.0μM. These values are promising when compared to the current cholinesterase inhibitors used for treatment of patients with Alzheimer's disease, to counteract the acetylcholine deficiency in the brain. Good correlation was obtained between IC50 data and results by molecular docking calculation on the binding interactions within the acetylcholinesterase active site, which also indicated the moieties in discorhabdin structures involved. To avoid unwanted peripheral side effects that can appear in patients using some acetylcholinesterase inhibitors, electrophysiological experiments were carried out on one of the most active of these compounds, discorhabdin G, which confirmed that it had no detectable undesirable effects on neuromuscular transmission and skeletal muscle function. These findings are promising for development of cholinesterase inhibitors based on the scaffold of discorhabdins, as potential new agents for treatment of patients with Alzheimer's disease.